The The Mediating Role of Sustainable Development Goals Disclosure in the Effect of Sustainability Performance on Financial Performance - Fifi Sisilia; Fitri Laila Wijayati (Relevance: Journal of Management and Business, 2026)
This study examines the mediating role of Sustainable Development Goals (SDGs) Disclosure in the effect of Sustainability Performance on Financial Performance. Tested within an emerging market context such as Indonesia—where investor behavior and regulations (e.g., POJK No. 51/2017) differ from those in developed nations—this research addresses a gap in the literature by positioning SDG disclosure as a specific mediator rather than focusing on direct effects or general ESG metrics. Using purposive sampling, a sample of 60 companies listed on the Indonesia Stock Exchange and ranked by the BGK Foundation was selected for the 2021–2024 period, yielding 240 observations. Panel GLS analysis was applied to ensure valid estimates despite violations of classical assumptions. The results indicate that both Sustainability Performance and SDGs Disclosure have a negative effect on Financial Performance. Conversely, Sustainability Performance positively affects SDG Disclosure. Crucially, SDGs Disclosure negatively mediates the effect of Sustainability Performance on Financial Performance.